Ecological Restoration Capacity Of River Nakiyanja Wetland System From The Effects Of Motor Vehicle Washing Bays, Along River Nakiyanja, Central Uganda - Turyahabwe, Remigio; Andama, Edward; Masaba, Sowedi; Andrew, Mulabbi; Alwin (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
Washing bays are associated with a wide range of contaminants, which end up in the water bodies, thereby contaminating and degrading water quality, hence affecting aquatic ecosystems. The research sought to study the impact of the motor vehicle washing bays on the ecology of the River Nakiyanja wetland system and assess the capacity of the wetland system to restore the ecosystem health from the effects of the washing bays. Data analysis employed the one-way ANOVA test. The findings revealed that the cumulative effects of degraded water quality on benthic macroinvertebrate assemblages were supported by low South African Score System –Average Score Per Taxon (SASS-ASPT) indices, and the resultant poor ecological status of the river at impact sites was compared to sites upstream and downstream of the washing bay. The SASS and resultant ASPT at the sampling sites differed significantly at P<0.05. The study findings further reveal that the River Nakiyanja wetland was capable of restoring over 60% of the ecosystem’s health. The study concludes that the Nakiyanja wetland has a high restoration capacity from the effects of motor vehicle washing bays. There is, however, a need to regulate motor vehicle washing bay activities by enforcing environmental legislation related to wastewater disposal to protect the River Nakiyanja.